Extraction of Lutein and Zeaxanthin Compounds from Sweet Potato Tuber Cilembu Cultivar (Ipomoea batatas L.) Integrated with the Production of Sweet Potato Flour with High Protein Levels - Theola Azarine, Astrid
The study was conducted to determine the effect of water content and solid to solvent ratio on the yield of lutein and zeaxanthin compounds extracted from the tuber of sweet potato Cilembu cultivar, using the One Factor at a Time (OFAT) method. Water content varied at 20, 11 and 5% and the solid to solvent ratio varied at 1:5, 3:10, and 2:5 (w/v). Extraction of lutein and zeaxanthin was carried out by the Soxhlet method using n-hexane as the solvent on a temperature of 65 oC for 4 hours, then the content of the compounds was determined based on the spectrophotometric method. The highest content of lutein and zeaxanthin compounds from sweet potato tubers were at 5% of moisture content and solid to solvent ratio of 2: 5 (w / v), with the values of 58,12 and 12,28 ?g/g dried substrate respectively. The residual extraction residue with a starch content of 78,4% was used as a substrate in the production of sweet potato tuber flour. In order to increase the levels of protein content, the flour was fermented by Aspergillus oryzae for 3 days at 30 oC in a roux bottle. Increased protein were quantified in variations with and without the addition of nitrogen source. 5% (w / w) of ammonium sulfate added as the nitrogen source. The highest protein content was obtained in the fermented flour with the addition of nitrogen source with a value of 13%. The productivity estimation of lutein extract, zeaxanthin extract, and sweet potato tuber flour were respectively 5,1, 1,04 and 648 x 102 kg / ha.year.